(untitled) (American Journal of Islam and Society, 2015)
The Summer Institute for Scholars 2015, held at the IIIT headquarters in Herndon, VA, from June 8-21, brought together a group of scholars to address “Constitutions and Pluralism in Muslim States and Societies.” In order to present as many of their ideas as possible, the wide-ranging and thought-provoking comments of the chairs and the discussants are not recounted here ...